Ossifying fibroma in the maxilla and orbital floor: Report of an uncommon case - Macedo, Diogo de Vasconcelos [UNESP]; Ferreira, Gabriely [UNESP]; Vieira, Eduardo Hochuli [UNESP]; Monnazzi, Marcelo Silva [UNESP] (The Korean Association of Oral and Maxillofacial Surgeons, 2020)
Benign fibro-osseous lesions occur when normal bone is replaced by cellular fibrous connective tissue and mineralized structures. One rare type of these lesions is the ossifying fibroma (OF). The aim of this study is to report an unusual case of OF in a 57-year-old female. Physical examination showed facial asymmetry without any tenderness, fluctuation, ocular pain, or ophthalmoplegia. Imaging exams revealed a solid mass involving the left maxilla and orbital floor. Surgical resection was performed without any complications or sequelae, and the histopathological results confirmed OF. Although recurrence is rare in this condition, the patient remains under follow-up.
Keywords: Maxilla; Orbit; Ossifying fibroma